2000
DOI: 10.1042/0264-6021:3480557
|View full text |Cite
|
Sign up to set email alerts
|

Atomic force microscopy of gastric mucin and chitosan mucoadhesive systems

Abstract: Atomic force microscopy has been utilized to probe, at a molecular level, the interaction between purified pig gastric mucin (PGM) and a mucoadhesive cationic polymer, chitosan (sea cure 210+), with a low degree (approx. 11%) of acetylation. Images were produced detailing the structures of both PGM and chitosan in 0.1 M acetate buffer (pH 4.5), followed by the complex of the two structures in the same buffer. PGM in 0.1 M acetate buffer revealed long linear filamentous structures, consistent with earlier elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 8 publications
4
46
0
1
Order By: Relevance
“…While it has been shown that electrostatic interaction is a major factor in the adhesion of cationic chitosan to purified anionic pig mucin (36), charge-based interactions of polymers with mucus remains poorly understood. The main adhesive interactions between adhesive polymers and mucus occur via covalent bonding, hydrogen bonding and electrostatic and hydrophobic interactions or a combination of these (41).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been shown that electrostatic interaction is a major factor in the adhesion of cationic chitosan to purified anionic pig mucin (36), charge-based interactions of polymers with mucus remains poorly understood. The main adhesive interactions between adhesive polymers and mucus occur via covalent bonding, hydrogen bonding and electrostatic and hydrophobic interactions or a combination of these (41).…”
Section: Discussionmentioning
confidence: 99%
“…Notable targets for tensile tests have included isolated thawed bovine duodenal (32), porcine esophageal (34), and rat intestinal tissue (35). Recently, atomic force microscopy has been used to quantitatively measure and image polymer interaction with mucin (36), although this technique has yet to be applied to mucus-producing epithelia. In addition, mucoadhesion of microparticles comprising fluorescent polycarbophil to isolated fresh porcine intestinal mucosa has recently been assessed in a flow-through system using phosphate buffer (37).…”
Section: Discussionmentioning
confidence: 99%
“…This has been one of the main reasons for its wide applicability to the encapsulation of different molecules such as DNA and antigens. Chitosan is also known to be mucoadhesive (37). At physiological pH, sialic acid molecules present in mucus have a negative charge, and, as a consequence, positively charged chitosan exerts strong electrostatic interaction with them.…”
Section: Nanoemulsionmentioning
confidence: 99%
“…3c) and loaded them with DNA containing pRc/ CMV-HBs(S). Chitosan is known for its mucoadhesive properties (37); thus, the addition of this polymer to the formulation is advantageous for creating an intranasal formulation with prolonged local retention. To test the immunological response, mice were immunized with glycol chitosan-coated liposomes loaded with DNA, as well as with naked DNA (i.n.…”
Section: Delivery Systems For Mucosal Immunizationmentioning
confidence: 99%
“…The particles were either post coated with chitosan, or chitosan was introduced in the particle production process, to achieve the partial or complete mucoadhesive chitosan coating of the particles. The ability of chitosan to form strong electrostatic interaction with mucus or a negatively charged mucosal surface has been described by different authors (29)(30)(31). It was found that chitosan could provide longer residence times for a dosage form on mucosal tissues and rapid absorption of the drug from the bioadhesive delivery system, avoiding its dilution or degradation (27,32).…”
Section: Introductionmentioning
confidence: 97%